RELEVANSI PENDIDIKAN KURIKULUM MERDEKA BELAJAR DENGAN PEMIKIRAN SAINTIS MUSLIM IBNU SINA DAN IBNU RUSYD - Sahrul Muhamad; Indah Rahmayanti; Muhammad Fadli Ramadhan (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Thisi researchi was iconducted because it was motivated to conduct deeper research iregarding thei relevance of the Merdekai iCurriculum and thei thoughts of Muslim scientists namely Ibn Sina and Ibn Rusyd. In this research, will examine thei valuesi ​​contained in the iMerdeka Curriculum, to then be associated with the thought of the concept of education by Muslim scientists Ibni Sinai andi Ibn iRushd, so ithat irelevance ican ibe ifound ibetween ithe itwo. iThis itype of iresearchi is idescriptive-iqualitative iresearch, imeaning ithat ithe iresearch isi presented in a descriptive manner using a philosophical iapproach, theiresearch imethod iused ini ithis researchi is library iresearch. Next, ithe idata isi ianalyzed using the content analysis method to select, compile data irelated ito ithe iMerdeka Curriculum, itheieducationalithoughts of Ibni iSina andi IbniiRushd and their relevance. iThe iresults iof ithe istudy iconclude that, in terms of ithe concepti ofi educationi puti iiforwardi iby ithe itwo Muslimi iscientists, it is relevant to the educational values ​​offered by the Merdeka iCurriculum, first in terms of purposes which emphasize aspects of character and competence, the second is the subject of education that is based on independence, the third is educational content thati itakes intoi iaccount the characteristics of students, and the fourth the educational method leads to a gradual teachingi andi learningi process. Seeing the characteristics of the purposes, subjects, contents, and methods put forward by Ibnu Sina and Ibnu Rushd, it is clear that the thoughts of these Muslim scientists are still relevant to the current curriculum in Indonesia, namely the Merdeka Curriculum.